Trypanosoma brucei: Composition, organisation, plasticity, and differential transcription of NlaIII repeat elements in drug-resistant and sensitive isolates - Jamnadass, Ramni H.; Pelle, Roger; Pandit, P.; Ricard, B.; Murphy, N.B. (Elsevier, 2006)
A Trypanosoma brucei brucei DNA repeat sequence termed NlaIII repeat (NR) was originally isolated from a multidrug-resistant field isolate CP547 [Jamnadass, R., 1995. Identification and characterisation of an extrachromosomal element from a multidrug-resistant isolate of T. brucei brucei, Ph.D. thesis, Brunel University, UK]. Subsequently studied in a laboratory strain (Tb427) [Alsford, N.S., Navarro, M., Jamnadass, H.R., Dunbar, H., Ackroyd, M., Murphy, N.B., Gull, K., Ersfeld,K., 2003. The identification of circular extrachromosomal DNA in the nuclear genome of T. brucei. Molecular Microbiology 47, 277-288], NRs were exclusively episomal. Here we show that NR sequences in CP547 are present on linear chromosomes as well as on episomal circular elements. Sequence analysis shows that NRs are composed of three classes of sub-repeat arranged in a specific order. Heterogeneity in size and sequence of an episomal 6.6 kbp element was shown in successive passages of the original CP547 isolate and derived clones in mice. Its copy number was unstable and was affected by selective pressure with the trypanocide diminazene aceturate. Some of the extrachromosomal elements appear to be composed of RNA-DNA hybrids. NR sequences were transcribed in a developmentally regulated manner but transcripts did not contain the spliced-leader sequence found on all trypanosome mRNAs.